Examining Narrative Text as The English Practicum Assessment in Junior High School - Metriyandani, Azka Amara; Paraswati, Hazlinda; Rohmana, Wahyu Indah Mala (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2024)
This study aims to find out the implementation of Narrative Text as the English Practicum Assessment in Junior High School and the challenges in learning English literature in secondary school as the English Practicum Assessment. This research used a qualitative descriptive method to determine teachers' methods and techniques in teaching and learning English using literature in school. Based on the result of the interview, the teacher describes the implementation of Narrative Text as the English Practicum Assessment in Junior High School. The teacher used storytelling for the material practicum assessment. Meanwhile, the teacher found the challenges in learning English literature in secondary school, such as the English Practicum Assessment. The challenges experienced include the students' difficulty in pronunciation, lack of vocabulary mastery, and need to be constrained by grammar. Narrative Text as the English Practicum Assessment in Junior High School to encounter the problems that impede the implementation of narrative Text in the practicum assessment, and from this reflection, researchers can find out the results of the literature used in the practicum assessment in Junior High School by using storytelling which the program has a positive impact on enhancing students' language abilities, particularly in English.